"Urban audit" - problemy pomiaru jakości życia w wybranych miastach Europy - Obrębalski, Marek ("Urban Audit" - problems of measurement of life quality in selected European cities, 2006)
Nowadays the demand for information on the quality of life in European urban areas is considerably growing. The quality of urban life is becoming a more and more important sub product of individual cities in our era of omnipresent competition. Therefore the demand for urban life quality audit is reported primarily by authorities of various levels. The European Commission launched two projects called Urban Audit. These projects involved large and middle towns through-out the EU and also Bulgaria and Romania. In the “Urban Audit II” survey each of 258 towns was assessed through 25 groups of indicators covering nine areas: demography, social aspects, economic aspects, civic involvement, education and training, environment, journeys and transport, information society and culture and leisure activities. The indicators were selected on the basis of availability and comparability criteria. An effective approach to measurement and assessment of the quality of city life requires easy access to a large range of varied but comparable information. Therefore all deficiencies in this sphere limit and obstruct the possibility of complex and objective assessment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1105, s. 99-110